(untitled) (Dhaka University Journal of Science, 2024)
The role of early years of a child’s life has a far-reaching impact in shaping lifelong outcomes. This paper has investigated the skill development of children aged between 36 and 48 months in Bangladesh to determine its association with the parenting attitude along with some child and maternal characteristics. The data from the latest round of Multiple Indicator Cluster Surveys (MICS 2019) are used for the analysis. The analytical approach constituted three separate binary logistic regression models (respectively for physical skills, social skills, and cognitive skills) to identify the behavioral associates of the child development. The findings depict child beating as a potential determinant for the obstructed physical skill development whereas spending the quality time with children is found to enhance social skills. Some other significant factors of the child development include division, weight of child, mother’s media exposure, and wealth index. Hence, this study has suggested some policy implications to strengthen preventive programs on child abuse, promote parent-child interaction, and encourage maternal media exposure to mitigate early childhood developmental barriers. Dhaka Univ. J. Sci. 72(2): 34-44, 2024 (July)